Sanguisorba officinalis L.inhibits process of exacerbating fibrosis in Choline deficient, L-amino acid defined, high-fat diet-fed mice - Nam, Yunseong; Kim, Myungsuk; Erdenebileg, Saruul; Park, Sun Young; Nho, Chu Won (KSBMB International Conference 2022, 2023)
Non-alcoholic steatohepatitis (NASH) is a disease that causes inflammation and damage in the liver due to fat accumulation. It is also known that the chances of recovering from NASH decrease dramatically in the developed fibrosis stage. Sanguisorba officinalis L. (SO) is a plant that has been traditionally used as anti-inflammatory and antioxidant effects and has beneficial effects related to metabolic diseases such as obesity and diabetes. This study aimed to confirm the efficacy of inhibiting NASH and fibrosis in vivo using 95% ethanol SO extract. SO extract was administrated orally to C57BL/6J mice fed a Choline deficient, L-amino acid defined, high-fat diet (CDAHFD) for 10 weeks. CDAHFD fed mice developed NASH and fibrosis, with minimal weight loss. Liver fibrosis area was quantified using Sirius Red staining, which was significantly reduced 40% by SO extract than CDAHFD fed group. In addition, fibrosis-related mRNA expressions of Col1a1, Col3a1, and Tgfb1 were significantly reduced by SO extract compared to the CDAHFD fed group. Furthermore, SO extract increased the mRNA expression of antioxidant enzymes and decreased level of malondialdehyde, lipid peroxidation marker, in liver. These results show that SO extracts may be effective in inhibiting the process of exacerbating fibrosis in NASH.